2020
DOI: 10.1111/acel.13189
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by which autophagy regulates memory capacity in ageing

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 59 publications
5
30
1
1
Order By: Relevance
“…Thus, dietary Spd-S is obviously able to boost hypusination levels in the aged mammalian brain. Notably, the mitochondrial status of mossy fiber synapses was also age-protected by Spd-S (Maglione et al, 2019), and Spd-S was found to protect cognitive performance in aging mice (De Risi et al, 2020) (see also accompanying paper in this issue of Cell Reports by Schroeder et al [2021], their Figure 2C). Our findings described here should thus be of relevance concerning the physiological and molecular basis for the mechanistic exploration and therapeutic usage of Spd-S effects.…”
Section: Cell Reportsmentioning
confidence: 96%
“…Thus, dietary Spd-S is obviously able to boost hypusination levels in the aged mammalian brain. Notably, the mitochondrial status of mossy fiber synapses was also age-protected by Spd-S (Maglione et al, 2019), and Spd-S was found to protect cognitive performance in aging mice (De Risi et al, 2020) (see also accompanying paper in this issue of Cell Reports by Schroeder et al [2021], their Figure 2C). Our findings described here should thus be of relevance concerning the physiological and molecular basis for the mechanistic exploration and therapeutic usage of Spd-S effects.…”
Section: Cell Reportsmentioning
confidence: 96%
“…Beclin-1 is an important autophagy mediator, which increases autophagy ( 40 ). Furthermore, it has been reported that ATG7 promotes autophagy ( 41 ), while p62 is negatively associated with the autophagy process ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps because studies attempting to deliberately overload memory in humans or experimental animals are practically non-existent. That said, very recent studies by De Risi et al suggest that week-long memory capacity in aged cognitively impaired mice is limited by an autophagic process that eliminates fibrils of Aβ and α-syn (De Risi et al, 2020). However, studies such as this are unusual, obliging one to look to correlative evidence.…”
Section: What Evidence Supports a Memory Overload Hypothesis?mentioning
confidence: 99%
“…If this is the case, then more natural, stimulating and highly enriched living environments in which animals are housed over a lifetime will be key to producing more valid experimental models. As will be using more demanding cognitive tests, such as that employed by De Risi colleagues introduced above (De Risi et al, 2020).…”
Section: What Evidence Supports a Memory Overload Hypothesis?mentioning
confidence: 99%